Domains of Indigenous Cinema: - Marcos Aurélio Felipe (Revista Brasileira de Estudos da Presença, 2024)
This study analyzes the place of indigenous peoples in documentary film, outlining the limits and possibilities that define their condition as subject or object of the documentary film. Based on cinema and anthropological studies, it identifies the extent to which the problem of the constitution of the subject in indigenous cinema allows us to consider a similar research question in the field of humanities. Between the historical and cosmological worlds, the audiovisual field and ante-field, permanent colonialism and counter-coloniality, the domains of power in the indigenous documentary perspective are invariably marked by tensions, fissures and limits. Who, after all, is the Other as subject and/or object of the camera?